Field and Frequency Dependence of the Dynamic Hysteresis in Lead Zirconate Titanate Solid Solutions. Issue 1 (28th November 2013) - Chen, Xuefeng; Dong, Xianlin; Cao, Fei; Wang, Junxia; Wang, Genshui; Damjanovic, D.
<x xml:space="preserve">Abstract</x> Dynamic hysteresis of Nb‐doped Pb(Zr1−xTix)O3 (PZT, 0.20 ≤ x ≤ 0.60) ceramics were studied systemically at different field (E) and frequency (f). The hysteresis loops were strongly dependent on E and f. The measured coercive fields (Ec0) were far lower than the calculated values based on the Landau–Ginzburg theory, and increased dramatically from the rhombohedral phase to the tetragonal phase while had less variation with composition in the same phase. With increasing E or f for each composition, three types of loops were observed: linear, minor, and saturated loops. The cross fields (E0), cross polarizations (P0), and hysteresis areas () showed different variation regularities with f. Similar varying curves were observed for all PZT ceramic samples by normalizing E0, P0, and with E/Ec0, which indicated the same polarization switching for different domain structures. Further analyses revealed that the switching processes can be divided into three stages: space charge polarization, domain switching, and steady state. The first and second stage occurred at ~0.5 and ~1.5 E/Ec0, respectively. These results would be very helpful to further understand the polarization switching of ferroelectric ceramics.